Pengaruh Current Ratio (CR) dan Debt To Assets Ratio (DAR) Terhadap Rerurn On Assets ( ROA) Pada Perusahaan Properti dan Real Estate yang Terdaftar Di Bursa Efek Indonesia Periode 2015 -2022 - Sawukir, Sawukir; Nurmono, Nurmono (RJABM (Research Journal of Accounting and Business Management), 2024)
The aim of this research is to determine the effect of Current Ratio (CR) and Deb To Assets Ratio (DAR) on Return On Assets (ROA) in property and real estate companies listed on the Indonesia Stock Exchange for the 2015-2022 period. The method used is a quantitative method using secondary data in the form of financial reports of property and real estate sector companies. The population in this study was 22 companies, using purposive sampling techniques, to obtain 4 property and real estate sector companies registered on the IDX that met the criteria. Data analysis uses a panel data regression model with the estimation used, namely the Fixed Effect Model (FEM). The research results show that partially the Current Ratio (CR) and Debt to Asset Ratio (DAR) do not have a significant effect on Return On Assets (ROA). Meanwhile, simultaneously, the Current Ratio (CR) and Debt to Asset Ratio (DAR) have a significant effect on Return On Assets (ROA) in property and real estate sector companies listed on the Indonesia Stock Exchange for the 2015-2022 period.